Knowledge Sharing Among Lecturers: Evidence from Indonesia - Nurpatwikanto, Widyo; Fikrianoor, Kahfi; Rolanisa, Prila Eki; Ulfa, Dian Maria; Latoe, Vega Anindhitha; Handayani, Wuri (Faculty of Economics and Business, Universitas Gadjah Mada, 2025)
Introduction/Main Objectives: This research aims to (a) investigate the impact of leadership types (specifically responsible and transformational leadership) on behavior related to knowledge sharing and (b) assess the influence of mediating factors of person-organization fit between leadership style and knowledge sharing behavior, and (c) examine how the culture of higher education institutions (HEIs) influences the development of leadership and organizational dynamics. Background Problems: In prior research, conflicting findings have emerged concerning the connection between leadership and knowledge sharing. It is essential, by looking at responsible and transformational types of leadership, to determine which type exerts the most substantial influence on knowledge-sharing behavior Novelty: This research extends previous research by utilizing two types of leadership, namely responsible leadership (RL) and transformational leadership (TL), in one research model. By doing this, we compare which of the two leadership models significantly influences knowledge-sharing behavior among lecturers. Research Methods: This research was conducted through an using convenience and snowball sampling methods and collected 256 lecturers as participants from diverse Indonesian universities. The data ware analyzed using partial least squares (PLS) with the support of WarpPLS 7.0. Finding/Results: This study discovered that responsible leadership, transformational leadership, and person-organization fit positively impact knowledge-sharing behavior. Moreover, the culture of higher education institutions moderates the relationship between responsible and transformational leadership and person-organization fit, however unfortunately, it fails to strengthen this relationship. Person-organization fit serves as a mediator in the relationship between transformational leadership and knowledge-sharing behavior. Additionally, it was observed that transformational leadership has a more significant impact than responsible leadership on knowledge-sharing behavior. Conclusion: This study has the potential to offer empirical evidence and bring cohesion to social exchange theories concerning the influence of leadership types on knowledge-sharing behavior